Divination and prediction in early China and ancient Greece - Raphals, Lisa (Cambridge Univ. Press, 2013)
"Divination was an important and distinctive aspect of religion in both ancient China and ancient Greece, and this book will provide the first systematic account and analysis of the two side by side. Who practised divination in these cultures and who consulted it? What kind of questions did they ask, and what methods were used to answer those questions? As well as these practical aspects, Lisa Raphals also examines divination as a subject of rhetorical and political narratives, and its role in the development of systematic philosophical and scientific inquiry. She explores too the important similarities, differences and synergies between Greek and Chinese divinatory systems, providing important comparative evidence to reassess Greek oracular divination"--